Aboriginal and Torres Strait Islander Social and Emotional Wellbeing and Mental Health. (August 2017) - Calma, Tom; Dudgeon, Pat; Bray, Abigail
Abstract : Closing the Aboriginal and Torres Strait Islander mental health gap is an urgent national priority. This commentary provides both an overview of Aboriginal and Torres Strait Islander social and emotional well being and mental health and some of the promising initiatives for restoring wellbeing. Solutions for addressing Aboriginal and Torres Strait islander mental health issues require a "best of both worlds" approach which acknowledges the impact of social and cultural determinants on Aboriginal and Torres Strait Islander wellbeing.